RETHINKING THE ROLE OF GOVERNMENT IN THE ECONOMY OF THE 21ST CENTURY: ANALYSIS BASED ON TRADITIONAL STATE PROGRAMS - Kud, Aleksandr, (Pressing Problems of Public Administration, 2021)
The paper offers the author’s view of the new role of the government in the economy of the 21st century, which is due to the fact that the former and current models of cooperation between the government and the market are unable to overcome regular “market failures” and “government failures”. After reviewing the modern literature and relying on Richard Thaler’s economic theory of “behavioral nudges”, the author critically considers the possibility of replacing a part of state social programs with alternative sources programs. The author has come to a conclusion that the state should be considered as a subject with greater autonomy than it has today and that performs certain functions as well as uses the financial resources available to it. In the near future, other tools besides taxes and government budget expenditures will be of greater significance; they are regulation tools, first of all. It is much closer to the role the 20th century government had. However, this role will be of a different kind. Nevertheless, regulation will be aimed at helping people and ensuring their right without forcing services.